Active fault tolerant control of buildings for seismic loads in finite frequency domain. Issue 10 (October 2015) - Zhu, Bohao; Lin, Weiyang; Zhan, Qian; Sun, Weichao; Hayat, Tasawar; Alsaadi, Fuad
Abstract This paper deals with the problem of vibration suppression for seismic-excited buildings in finite frequency domain, and the possible faults caused by actuators are also considered in controller׳s design to improve the stability of the system. Firstly, with the consideration of seismic wave׳s effect, a mathematical model of building structure system is established. Then the finite frequency theory is introduced to the process of controller design in order to reduce seismic-excited building vibration over a certain frequency band and enhance disturbance suppression performance. Furthermore, taking actuators׳ faults into account, the active fault tolerance control method is also added to the finite frequency domain controller to compensate for the faults effect and remain the performance of building system at an acceptable level when faults occur. Finally, simulation of a three-degree-of-freedom linear building structure under earthquake excitation is given to illustrate the effect of the proposed approach.